Synthesis and studies of crowned dipyrromethenes based macrocycles. Issue 46 (15th November 2019) - Ojha, Belarani; Kumar, Ankit; Thorat, Kishor G.; Ravikanth, Mangalampalli
Abstract: Three different meso -substituted new type of crowned dipyrromethene macrocycles were synthesized in decent yields over a sequence of four simple reaction steps using readily available precursors. The macrocycles were thoroughly characterized by HRMS as well as 1D and 2D NMR spectroscopic techniques and the structures of one of the macrocyles in its neutral form and protonated form were determined by X-ray crystallography. The crystal analysis indicated that the macrocycle was distorted in both neutral and protonated forms owing to the presence of flexible aliphatic ether chain. Absorption and electrochemical studies indicated that the properties of macrocycles were dependent on type of aryl group present at the meso -position of dipyrrin moiety of crowned dipyrromethene macrocycle. The preliminary studies indicated that the crowned dipyrromethene macrocycles can act as specific colorimetric optical sensor for Cu 2+ ion. Graphical abstract: Image 1 Highlights: First report on synthesis of crowned dipyrromethene based macrocycles. Structure was confirmed by NMR, HRMS and Crystallography Crowned dipyrromethene macrocycles acts as specific colorimetric sensor for Cu 2+ ion.